Trends and factors associated with anemia among women of reproductive age in Mali: analysis of data from 2001 to 2018 Mali demographic and health surveys - Ebenezer Kwesi Armah-Ansah; Eugene Budu; Charity Oga-Omenka; Marina Kolosnitsyna (Archives of Public Health)
Abstract Background Even though widespread attempts have been made to halve the incidence of anemia by 2025, the prevalence remains alarmingly high among women of reproductive age in Africa. The government of Mali has underscored the necessity for a multi-sectoral approach to reducing the anemia burden. However, no studies have considered the trends and factors associated with anemia among women of reproductive age in Mali. Hence, this study examined the prevalence and trends of anemia among women of reproductive age in Mali from 2001 to 2018. Methods The study analyzed datasets from the 2001, 2006, 2012–2013, and 2018 Mali Demographic and Health Surveys. We included a total weighted sample of 18,096 women of reproductive age who had participated in the hemoglobin test. Multilevel regression analysis was employed, and the results were presented as adjusted odds ratio (aOR), with 95% confidence intervals (CIs) and p-values used to show the results. Results We found that anemia prevalence in Mali remained persistently high, with a marginal increase from 63.4% in 2001 to 63.5% in 2018. The overall prevalence of anemia among women of reproductive age in Mali from 2001 to 2018 was 59.3% [95% CI: 58.2–60.4%]. We found, however, that about 2.6% were severely anemic. The study found that women of reproductive age who have secondary and above education [aOR = 0.75, 95% CI = 0.67–0.84], overweight women [aOR = 0.62, 95% CI = 0.55–0.70], women in the richest wealth quintile [aOR = 0.83, 95% CI = 0.71–0.97], women who have improved sources of drinking water [0.91, 95% CI = 0.84–1.10], women who lived in the Kidal Region [aOR = 0.38, 95% CI = 0.30–0.49], and women of reproductive age who lived in communities with medium literacy [aOR = 0.80, 95% CI = 0.73–0.87] had lower odds of being anemic. However, women who were captured in the 2018 survey year [aOR = 1.23, 95% CI = 1.11–1.37], women with four or more births [aOR = 1.15, 95% CI = 1.02–1.30], and women who were pregnant [aOR = 1.57, 95% CI = 1.42–1.73] had higher odds of developing anemia. Conclusion The prevalence of anemia among women of reproductive age in Mali remains alarmingly high and virtually unchanged in 17 years. To address this persistent public health challenge, coordinated action is necessary. The government and public administrators should prioritize strengthening antenatal care services through free maternal health care, iron supplementation, treated mosquito nets, and deworming programs. Additionally, the Ministry of Water and Sanitation, in collaboration with traditional leaders and community health authorities, must ensure that every household has access to protected, potable drinking water. Finally, the Ministry of Education and the Ministry of Health and Public Hygiene should jointly develop targeted health and nutrition interventions and programs that would mitigate anemia prevalence among women of reproductive age in Mali. Without these concerted efforts, this significant public health burden is likely to persist.